Towards the maturity stage an insight into the performance of French technopoles - Chorda, Isidre March (Technovation)
This study contains an insight into the current situation exhibited, in France, by a set of territorialized initiatives known as technopoles, as a way of learning valuable lessons about similar initiatives and projects still in their preliminary stages and prior to their full launching process.